Role of aspirin in the prevention of preeclampsia in previously hypertensive pregnant women: a meta-analysis - Syed Muhammad Ashraf Jahangeer; Ashraf Khan, Asma; Mansoor, Mahnoor (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the role of low-dose aspirin in preventing preeclampsia for previously hypertensive pregnant women. Method: The meta-analysis was conducted from February to May 2021 and comprised search on PubMed and Cochrane Library databases for randomised controlled trials consisting of previously hypertensive women aged 18-55 years, aspirin dosage range 60-100mg, and a comparison between aspirin and placebo groups. Duration of intervention till the end of gestation, the dosage of aspirin given, risk ratios or odds ratio with the confidence intervals, and preeclampsia were the main variables recorded. Data was analysed using RevMan 5.4. Result: Of the 144 articles found, 4(%) were included, having 2238 participants. Pooled estimates revealed that aspirin, compared to placebo, did not significantly reduce the manifestation of preeclampsia (p=0.06). Besides, heterogeneity between the different trials was moderate at 59%. Conclusion: Aspirin was not found to substantially diminish the risk of incidence of preeclampsia, but it did show some beneficial effects. Key Words: Preeclampsia, Low-dose aspirin, Hypertensive pregnant women.